2017
DOI: 10.3762/bjnano.8.225
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative electron attachment to coordination complexes of chromium: chromium(0) hexacarbonyl and benzene-chromium(0) tricarbonyl

Abstract: Here we report the results of dissociative electron attachment (DEA) to gas-phase chromium(0) hexacarbonyl (Cr(CO)6) and benzene-chromium(0) tricarbonyl ((η6-C6H6)Cr(CO)3) in the energy range of 0–12 eV. Measurements have been performed utilizing an electron-molecular crossed beam setup. It was found that DEA to Cr(CO)6 results (under the given experimental conditions) in the formation of three fragment anions, namely [Cr(CO)5]−, [Cr(CO)4]−, and [Cr(CO)3]−. The predominant reaction channel is the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…As also observed for W(CO) 6 [15,19,20], but in contrast to Cr(CO) 6 [16,17,19,20] and Fe(CO) 5 [51], the series of CO loss is not complete [19,20] and there is no formation of the bare metal anion. The intensities of the DEA curves in Figure 1 reflect the relative efficiencies of these reaction channels [15][16][17]19,20]. This is shown in Table 1 along with the peak maxima observed in the ion yields for individual fragments in the current study and those reported by Winters and Kiser [19] and by Pignataro and co-workers [20].…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…As also observed for W(CO) 6 [15,19,20], but in contrast to Cr(CO) 6 [16,17,19,20] and Fe(CO) 5 [51], the series of CO loss is not complete [19,20] and there is no formation of the bare metal anion. The intensities of the DEA curves in Figure 1 reflect the relative efficiencies of these reaction channels [15][16][17]19,20]. This is shown in Table 1 along with the peak maxima observed in the ion yields for individual fragments in the current study and those reported by Winters and Kiser [19] and by Pignataro and co-workers [20].…”
Section: Resultssupporting
confidence: 64%
“…Resonant electron capture at threshold is clear in the electron transmission spectra from Giordan et al [18] indicating that in the study by Winters and Kiser [19] this might be an artifact rooted in lack of low-energy electrons from the ionization source of the mass spectrometer used in their study. This is further supported by the fact that the peak maxima for single CO loss from other metal carbonyls reported by Winters and Kiser are all close to 2 eV, while more recent studies [15][16][17] and the study by Pignataro and co-workers [20] report single CO loss from these compounds close to 0 eV. A further indication is in the relative abundance ratios of 100:65 reported by Winters and Kiser [19] for [Mo(CO) 5 ] − vs [Mo(CO) 4 ] − , while these are closer to 20:1 in the current study.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…This expectation is met by a novel fluorinated silver carboxylate precursor that yields deposits with so far unprecedented silver content including 3D structures [ 15 16 ]. However, given a favorable structure, even large organic ligands may be removed more easily than previously anticipated, as exemplified by the electron-induced dissociation of benzene–Cr(CO) 3 [ 17 ] and by FEBID using the fluorine-free precursor Cu(tbaoac) 2 [ 18 ]. The most elegant approach to precursor design yet is to use a bimetallic molecular structure to predefine, through the precursor stoichiometry, the composition of an alloy to be deposited by FEBID.…”
mentioning
confidence: 99%